Pyrinap ligands for enantioselective syntheses of amines - Qi Liu (Nature Portfolio, 2021)
Chiral amines find use as chiral ligands, resolving reagents and versatile building blocks as well as in pharmaceuticals and agrochemicals. Here, the authors developed Pyrinap ligands for the copper-catalyzed enantioselective A3-coupling of terminal alkynes, aldehydes, and amines affording optically active propargylic amines.